Forestry Management Practices in Mizoram - a Review - Garbyal, S. S. (Indian Forester, 1996)
Wide spread shifting cultivation and lack of scientific management have cleared and greatly altered the original tropical evergreen forests of Mizoram and turned them into secondary bamboo forests and open grasslands with scattered tree growth. Unless timely actions are taken to delineate and consolidate the forests and bring them under proper scientific management the forests will remain untended and unprotected.